2012
DOI: 10.1158/1078-0432.ccr-12-0234
|View full text |Cite
|
Sign up to set email alerts
|

CD20+ Tumor-Infiltrating Lymphocytes Have an Atypical CD27− Memory Phenotype and Together with CD8+ T Cells Promote Favorable Prognosis in Ovarian Cancer

Abstract: Purpose: Tumor-infiltrating lymphocytes (TIL), in particular CD8þ T cells and CD20 þ B cells, are strongly associated with survival in ovarian cancer and other carcinomas. Although CD8 þ TIL can mediate direct cytolytic activity against tumors, the role of CD20 þ TIL is poorly understood. Here, we investigate the possible contributions of CD20 þ TIL to humoral and cellular tumor immunity.Experimental Design: Tumor and serum specimens were obtained from patients with high-grade serous ovarian cancer. CD8þ and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
360
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(417 citation statements)
references
References 52 publications
34
360
3
4
Order By: Relevance
“…CD20 C B cells contribute both to humoral immunity as antibody-producing cells, but also to cellular immunity by serving as antigen-presenting cells (APCs) and/or by providing costimulatory signals to T cells. 19,20 A favorable effect of tumor-infiltrating B cells on patient prognosis was previously reported in cutaneous melanoma, 21 breast cancer 22 and ovarian cancer, 23 but the mechanism linking the accumulation of these cells in the tumor microenvironment and better prognosis remains poorly understood. Nielsen et al found that tumor-infiltrating B cells expressed markers of antigen presentation and could have a function of professional APCs to support the T cell-mediated immune anticancer response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD20 C B cells contribute both to humoral immunity as antibody-producing cells, but also to cellular immunity by serving as antigen-presenting cells (APCs) and/or by providing costimulatory signals to T cells. 19,20 A favorable effect of tumor-infiltrating B cells on patient prognosis was previously reported in cutaneous melanoma, 21 breast cancer 22 and ovarian cancer, 23 but the mechanism linking the accumulation of these cells in the tumor microenvironment and better prognosis remains poorly understood. Nielsen et al found that tumor-infiltrating B cells expressed markers of antigen presentation and could have a function of professional APCs to support the T cell-mediated immune anticancer response.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al found that tumor-infiltrating B cells expressed markers of antigen presentation and could have a function of professional APCs to support the T cell-mediated immune anticancer response. 23 Another report underlines the capacity of B cells found in TLS to produce antibodies that specifically recognize tumor antigens. 24 In our series, we hypothesize that the anticancer effect of T-bet C T cells and CD20 C B cells could be balanced by the immunosuppressive action of Foxp3 C Tregs since a high intratumoral density of these particular immune cells are significantly associated with reduced RFS.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial involving more than 1000 patients revealed that, in patients receiving neoadjuvant chemotherapy, the broad infiltration of lymphocytes into tumors seemed to be more clinically beneficial than no lymphocytic infiltration, in terms of achieving a pathologic complete response after chemotherapy 54 . In conclusion, this study shows that elevated PLR is closely associated with poor survival outcome in patients with OC.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is therefore surprising that ELFs arise in tumours at all. However, ELFs have been described in numerous cancers including colorectal,60, 88 rectal,89 breast,67, 90, 91 ovarian67, 92 and germ cell93 cancers, as well as melanoma,62, 67, 94 mucosal‐associated lymphoid tissue lymphoma39 and non‐small cell lung carcinoma95, 96 (NSCLC; see Dieu‐Nosjean et al . for a comprehensive review of ELFs in cancer9).…”
Section: Elfs As Regulators Of Anti‐tumour Immunitymentioning
confidence: 99%